Development of an automatic heat control in chicken coop using Arduino Uno microcontroller / Muhammad Syamil Mohammad, Muhammad Khairol Akmal Mohamad Sanusi and Muhamad Aimannuddin Hasan Ashaari - Mohammad, Muhammad Syamil; Mohamad Sanusi, Muhammad Khairol Akmal; Hasan Ashaari, Muhamad Aimannuddin (2015)
This project aim to assist people who are rearing chicken by controlling the body temperature of the chicken in a coop. The objective of this project is to study the measurement of suitable temperature in chicken coop and use of arduino uno microcontroller. By developing an automatic heat control using microcontroller, this will assist entrepreneur to use new technology in chicken farming. This project consists of using temperature sensor which is LM35 to detect the temperature. When the temperature below 29°C ac lamp will turn ON. Otherwise, when the temperature above 33°C ac lamp will turn OFF. In conclusion, by developing this project this could lead to a new technique on chicken farming.